Ag@TiO2 Nanoprisms with Highly Efficient Near‐Infrared Photothermal Conversion for Melanoma Therapy. Issue 1 (5th December 2019) - Nie, Chuang; Du, Peng; Zhao, Hongwei; Xie, Hainan; Li, Yuxin; Yao, Li; Shi, Yuanyuan; Hu, Lianna; Si, Shaoyan; Zhang, Maonian; Gu, Jianwen; Luo, Ling; et al.
Abstract: Melanoma is a primary reason of death from skin cancer and associated with high lethality. Photothermal therapy (PTT) has been developed into a powerful cancer treatment technique in recent years. Here, we created a low‐cost and high‐performance PTT agent, Ag@TiO2 NPs, which possesses a high photothermal conversion efficiency of ≈65 % and strong near‐infrared (NIR) absorption about 808 nm. Ag NPs were synthesized using a two‐step method and coated with TiO2 to obtain Ag@TiO2 NPs by a facile sol‐gel method. Because of the oxide, Ag@TiO2 NPs exhibit remarkable high photothermal conversion efficiencies and biocompatibility in vivo and in vitro. Cytotoxicity and therapeutic efficiency of photothermal cytotoxicity of Ag@TiO2 NPs were tested in B16‐F10 cells and C57BL/6J mice. Under light irradiation, the elevated temperature causes cell death in Ag NPs‐treated (100 μg mL −1 ) cells in vitro (both p <0.01). In the case of subcutaneous melanoma tumor model, Ag@TiO2 NPs (100 μg mL −1 ) were injected into the tumor and irradiated with a 808 nm laser of 2 W cm −2 for 1 minute. As a consequence, the tumor volume gradually decreased by NIR laser irradiation with only a single treatment. The results demonstrate that Ag@TiO2 NPs are biocompatible and an attractive photothermal agent for cutaneous melanoma by local delivery. Abstract : Culture Club : In vitro experiments showed that cells can be killed by co‐culture with Ag@TiO2 and with laser irradiation. In vivo, Ag@TiO2 effectively eliminates subcutaneous melanoma tumor. These results suggest that Ag@TiO2 NPs possess stronger NIR absorption and photothermal conversion ability both in vivo and in vitro.